2017
DOI: 10.7602/jmis.2017.20.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision Robotic Cholecystectomy: Initial Experience and Results

Abstract: EDITORIALAlthough there have been many studies of the safety or feasibility of single-incision laparoscopic surgery (SILS) since it was first performed in 1997, 1 most surgeons agree that it has disadvantages such as difficulty conducting triangulation, instrument crowding, and collisions. [2][3][4] To overcome these limitations of laparoscopy, the robotic platform was developed, providing advantages including three-dimensional view, magnification, and an articulated instrument.5 However, robotic surgery requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“… 1 In the case of single incision laparoscopic cholecystectomy (SILC), studies have demonstrated several limitations such as collision between the laparoscopic instruments, problems in manipulating tissues or in delicate movements, the long learning curve, improper triangulation, and ergonomics. 2 , 3 RSSC, as a counterpart of SILC, is on the rise in minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 In the case of single incision laparoscopic cholecystectomy (SILC), studies have demonstrated several limitations such as collision between the laparoscopic instruments, problems in manipulating tissues or in delicate movements, the long learning curve, improper triangulation, and ergonomics. 2 , 3 RSSC, as a counterpart of SILC, is on the rise in minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the robotic single-site technology is non-wristed, and unlike other conventional robotic instruments, only provides rotation, the ergonomics are nevertheless excellent. 2 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…However, SSLC has been limited by poor visualization, lack of triangulation, and instrument collisions. Several studies have reported increased complications and incisional hernia occurrence in SSLC [1,2,5,6,13].…”
Section: Discussionmentioning
confidence: 99%
“…The robotic system also has instruments with 7° of movement, and any tremors are filtered out [8]. Others have proved that robotic cholecystectomy is a safe procedure without severe complications and gives improved cosmetic results [1,2,5,6,8,13]. The only drawback of robotic cholecystectomy is that it is expensive [2].…”
Section: Outcomes Of Single-site Cholecystectomymentioning
confidence: 99%
See 1 more Smart Citation